THE INFLUENCE OF PERSONALITY & TRAINING ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLES - Endang Roswita Gulo; Raden Teja Yokanan; Ade Kristianus Kaloeti (Dynamic Management Journal, 2023)
This study is the result of research that describes and analyzes how much factors affect personality, training, and performance with job satisfaction as an intervening variable in the Agriculture and Food Security Service of the Special Region of Yogyakarta. This type of research uses quantitative methods with data collection techniques using questionnaires distributed manually to 110 employees at the Yogyakarta Special Region Agriculture and Food Office. The sampling technique uses simple random sampling, which is a technique of taking samples from members of the population that is carried out randomly without regard to the strata in the population(Sugiyono, 2015). Based on the results of the study after previously conducting validity and reliability tests, it shows evidence that the first direct effect, namely; personality has a direct effect on performance; second, training has no direct effect on performance; third, personality has a positive effect on job satisfaction; fourth, training has a positive effect on job; and fifth, job satisfaction affects performance; while the sixth, the results of indirect effects show that personality affects performance through job satisfaction, and seventh; training affects performance through job satisfaction.